Quality of Life among Respondents Receiving Opioid Substitution Therapy in the Hospitals of Koshi Province - Pradhan, Uma; Mandal, Anjuly; Shrestha, Ashmita; Shrestha, Menuka; Subba, Dipty (Journal of Nursing and Health Sciences Nepal, 2025)
Introduction: Opioid Substitution Therapy (OST) is one of the safest and cost-effective treatments for the clients with opioid dependance. Studies have found that the quality of life of the respondents receiving OST has been significantly improved over the period of time. The objective of the study is to identify the quality of life (QOL) among respondents receiving Opioid Substitution Therapy in Hospitals of Koshi Province, Nepal. Methods: Quantitative cross-sectional design was adopted in the study. Total number of 105 respondents participated in the study from Koshi Hospital and Mechi Hospital. A standard tool WHOQOL-BREF was used to collect the data. Data was collected through in person interview. Ethical clearance was done by Purbanchal University School of Health Sciences-Institutional Review Committee (PUSHS-IRC). Manwhitney U test and Kruskal Wallis Test were used to find out the association of domains of quality of life with selected variables. SPSS version 16 was used for data analysis. Results: The median (IQR) value of quality of life was 66.0(59.62-73.5). There was significant association between environmental domain of QOL (p=0.028) with the age of the respondent. There was also a significant association of physical domain (p=0.026), social domain (p=0.026) and environmental domain (p=0.046) of QOL with duration of the Opioid Substitution Therapy. There was a significant association of Mental (p=0.008) and Environmental domain (p=0.002) of QOL with the level of education. Conclusion: Respondents in OST demonstrated better QOL in physical, social and mental domain in comparison to environmental domain. The domains of quality of life varied with the age, education of the respondent and the duration of Opioid Substitution Therapy.